(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2023)
In Bangladesh, a comprehensive study was conducted over one year to compare the reproductive and productive performance of Black Bengal, Jamunapari, and crossbred goats. The study involved a sample size of 226 goats and provided insightful information on the distinctive capabilities of each type of goat breeds. Most of the doe were 21–30 months of age, and their weight was 21–30 kg. The feed supply for the doe was concentrated green grass, whereas the kids got supplementary feed like rice bran. Among the reproductive traits, age at puberty, age of first kidding, and age of the first conception were significantly (P<0.001) higher in Jamunapari goats, whereas aerial kidding intervals were found in 263.77 ± 54.26 days in crossbreeds. Postpartum heat periods were highest at 68.50 ± 5.53 days in Jamunapari goats at 1st and 2nd parity, though at 3rd parity, 22.96 ± 26.66 days were uppermost in Black Bengal. There was no significant effect of parity on lactation length or milk production. Though Jamunapari goats show the highest lactation length at 1st and 2nd parity, at 3rd parity, 2.56 ± 2.89 kg was the largest in Black Bengals. The mortality of kids was high in the second parity in Black Bengal and crossbreeds, whereas in Jamunapari, it was higher in the first and second parities. The mortality rate of kids under 20 days was high, which gradually decreased with the advancement of age. Different periparturient and postpartum diseases, like abortion, dystocia, retained placenta, etc., decreased the reproductive performance of goats. The Black Bengal goat exhibited superior productive and reproductive performance to Jamunapari and crossbred goats. The study’s findings suggest that, in the southwestern region of Bangladesh, prioritizing Black Bengal goats for breeding programs could potentially enhance both productive and reproductive traits compared to Jamunapari and crossbred goats. Asian Australas. J. Biosci. Biotechnol. 2023, 8 (3), 78-87